Message from the President of Liberia Dr Samuel Doe on World Telecommunications Day (African Knowledges and the History Publication since the 1970s, 1987)
A message from the President of Liberia, Samuel Kanyon Doe, on the celebration of World Telecommunications Day 1987.
Keywords: President of Liberia